Gasification of biomass with oxygen-enriched air in a pilot scale two-stage gasifier. (15th June 2015) - Wang, Zhiqi; He, Tao; Qin, Jianguang; Wu, Jingli; Li, Jianqing; Zi, Zhongyue; Liu, Guangbo; Wu, Jinhu; Sun, Li
Highlights: Gasification of biomass with oxygen-enriched air in a pilot scale two-stage gasifier. Oxygen concentration has marked effect on the content of H2 + CO in the syngas. Oxygen concentration has little effect on the H2 /CO ratio in the syngas. A syngas with about 70 v% of H2 + CO and H2 /CO = 1 is obtained when using 99.5 v% oxygen. Abstract: Biomass gasification in a pilot scale two-stage gasification gasifier for BTL via one-step DME synthesis is developed. The effects of the concentrations of feeding oxygen and biomass species on the gasification temperature, gas composition, and carbon conversion efficiency are presented. The runs of the several tests show that a high and uniform temperature in the oxidation and reduction zones is generated in the gasifier with different oxygen levels. The oxygen levels in the gasifying agent have a marked impact on the content of H2 + CO in the syngas. However, the H2 /CO ratio is hardly impacted by the changes of oxygen levels, and the H2 /CO ratio is about 1 in all runs. The carbon conversion efficiency can reach 80% and a syngas containing more than 70 v% of H2 + CO and H2 /CO = 1 is obtained when 99.5 v% oxygen is employed. This syngas conform to the downstream application for one-step DME synthesis.